ASEAN's Myanmar snub - Desker, Barry (2022)
Withdrawing the welcome mat to junta leader Min Aung Hlaing from ASEAN’s summit is a much-needed signal on what is acceptable, even as ASEAN struggles with the multiple pressures posed by Myanmar.